2019
DOI: 10.3389/fonc.2019.01062
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Power of a Radiomic Signature Based on 18F-FDG PET/CT Images for EGFR Mutational Status in NSCLC

Abstract: Radiomics has become an area of interest for tumor characterization in 18F-Fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) imaging. The aim of the present study was to demonstrate how imaging phenotypes was connected to somatic mutations through an integrated analysis of 115 non-small cell lung cancer (NSCLC) patients with somatic mutation testings and engineered computed PET/CT image analytics. A total of 38 radiomic features quantifying tumor morphological, grayscale stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 65 publications
5
53
0
1
Order By: Relevance
“…Gender as only clinical characteristic was selected in combine model of our study. The addition of clinical characteristics to PET/CT radiomics model, to varying degrees, increase the diagnostic performance of diagnostic model in previous studies ( 22 , 23 ) and our study, which finally reached 82.6% of diagnostic accuracy in Li X’s study ( 22 ), 80.0% in Zhang J’s study ( 23 ), and 75.3% in our study for predicting EGFR mutation status. It suggested that the combined model might be an alternative indicator of EGFR mutations when tissue samples are not available.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Gender as only clinical characteristic was selected in combine model of our study. The addition of clinical characteristics to PET/CT radiomics model, to varying degrees, increase the diagnostic performance of diagnostic model in previous studies ( 22 , 23 ) and our study, which finally reached 82.6% of diagnostic accuracy in Li X’s study ( 22 ), 80.0% in Zhang J’s study ( 23 ), and 75.3% in our study for predicting EGFR mutation status. It suggested that the combined model might be an alternative indicator of EGFR mutations when tissue samples are not available.…”
Section: Discussionsupporting
confidence: 52%
“…In summary, the NSCLCs with EGFR mutation had lower glucose metabolism and density, with more heterogeneity on both PET and CT images than those with wild-type EGFR. Owing to the bi-modal image features, PET/CT radiomics model in recent studies (0.79 in Zhang J’s study ( 23 ); 0.80 in Li X’s study ( 22 ); 0.77 in our study) has showed higher AUC than those generated by PET (0.67 in Yip, SS’s study ( 21 )) or CT (0.69 in Rios Velazquez, E’s study ( 19 ); 0.56-0.75 in Sacconi, B’s study ( 31 )) radiomics features alone for predicting EGFR mutation status. However, compared with larger sample size in CT radiomics research, the current sample size in PET/CT radiomics-related studies is generally limited, and thus the generalization ability of PET/CT radiomics-based model remains to be further tested.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, presence of pleural effusion and a SUV entropy > 5. 36 were significantly associated with shorter PFS. The significant clinical and imaging variables in the univariate analysis were fitted into the multivariate Cox regression model.…”
Section: Univariate and Multivariate Cox Regression Analysismentioning
confidence: 87%
“…When combining with other accessible factors, an AUC of predicting EGFR mutations could reach 0.84. Several studies [8,[12][13][14][15][16][17][18][19][20][21][22][23] had evaluated the value of FDG uptake for predicting EGFR status in NSCLC. As described in Table 3, the results were not very consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Using FDG tumor uptake as a predictor of EGFR status could be worth exploring. Several studies have investigated the association between SUVmax and EGFR mutations [8,[14][15][16][17][18][19][20][21][22][23][24][25]. However, the results were controversial and conflicting.…”
Section: Ivyspringmentioning
confidence: 99%